Suppressing information storage in a structured thermal bath - Martins, Wilson Santana (2022)
Quantum system tend to have information lost from transmission through the correlations generated among degrees of freedom. For situations where we have a non-Markovian environment, the information contained in it may return to the system, and non-Markovian witnesses can capture such effect. In the present work, we sought how the environment structure affects the system information reachability since its finite size induces a quasiperiodic behavior in the decoherence and enables a highly non-Markovian behavior in the dynamics. To do that, we use a central qubit coupled to a spin chain with Ising interactions subject to a magnetic field, i.e., a central spin model, and solve the exact dynamics of the system. Moreover, we use two witnesses to analyze the presence of non-Markovianity: the Breuer-Laine-Piilo (BLP) trace distance-based measure and the conditional past-future correlator (CPF). On the other hand, we see how such behavior suppresses the classic plateau in Partial Information Plot (PIP) from the paradigm of quantum Darwinism and objective information from Spectrum Broadcast Structure (SBS). In addition to the system point of view, we show that the environmental structure avoids encoding accessible and distinguishable information for measurement in the environment for any model limit. Finally, he orthogonality between the density operators decodes the distinguishability between SBS states in the environment.